2017
DOI: 10.11648/j.ijefm.20170503.15
|View full text |Cite
|
Sign up to set email alerts
|

An AHP Based Approach to Identify and Eliminate Most Severe Risks of the Internal Supply Chain of Ready Made Garments (RMG) Industries: A Case Study

Abstract: Risk is a basic term for any decision making framework which can be defined as a probability or threat of damage, injury, liability, loss, or any other negative occurrence that is caused by external or internal vulnerabilities. For having a wide range of risks, Ready Made Garments (RMG) sector faces different difficulties in accomplishing their missions and goals. This paper has identified different risks associated with internal supply chain of the RMG sector. To achieve the expected outcome from this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The manufacturing metric (ST) of third category (AMM) is linked to its previous categories metrics and also linked to manufacturing fitness which is the determinant of manufacturing overall fitness (Mondal et al, 2017;Surana et al, 2005;Swafford et al, 2006). Due time shipment gives the evidence of proper handling of previous metrics and it motivates and encourages the employees for the better performance & growth of an organization (Rahman & Rahman, 2019;Swink et al, 2005), thereby senior management suggested the manufacturers to keep a focus on ST. Based on the evidences from the previous researches, this research proposed the following hypotheses.…”
Section: Hypotheses Proposition Between Dmm and After Manufacturing Mmentioning
confidence: 99%
“…The manufacturing metric (ST) of third category (AMM) is linked to its previous categories metrics and also linked to manufacturing fitness which is the determinant of manufacturing overall fitness (Mondal et al, 2017;Surana et al, 2005;Swafford et al, 2006). Due time shipment gives the evidence of proper handling of previous metrics and it motivates and encourages the employees for the better performance & growth of an organization (Rahman & Rahman, 2019;Swink et al, 2005), thereby senior management suggested the manufacturers to keep a focus on ST. Based on the evidences from the previous researches, this research proposed the following hypotheses.…”
Section: Hypotheses Proposition Between Dmm and After Manufacturing Mmentioning
confidence: 99%